2006
DOI: 10.1029/2006gl026581
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the temperature gradient instability as the source of decameter‐scale ionospheric irregularities on plasmapause field lines

Abstract: [1] Recent observations with the new mid-latitude SuperDARN HF radar located at Wallops Island, Virginia have identified a class of ionospheric irregularities that is prevalent in the nightside sub-auroral ionosphere under lowto-moderate Kp conditions. These irregularities can be observed for many hours and generally exhibit very low Doppler velocities. A recent collaborative experiment using the Wallops radar and the Millstone Hill incoherent scatter radar has determined that these irregularities are located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(91 citation statements)
references
References 10 publications
8
81
2
Order By: Relevance
“…The Hokkaido radar was constructed in Rikubetsu town, Hokkaido, Japan at 43.53°N and 143.61°E in geographic coordinates. The magnetic latitude (MLAT) is 36.46°and the L-value is 1.55 (c.f., the Wallops radar [e.g., Greenwald et al, 2006] [4] The line-of-sight Doppler velocity observation of the flow reversal region is summarized in Figure 1. The spatial extent of the flow reversal region is about 1.5 hour in magnetic local time (MLT) and 5°in MLAT.…”
Section: Observational Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hokkaido radar was constructed in Rikubetsu town, Hokkaido, Japan at 43.53°N and 143.61°E in geographic coordinates. The magnetic latitude (MLAT) is 36.46°and the L-value is 1.55 (c.f., the Wallops radar [e.g., Greenwald et al, 2006] [4] The line-of-sight Doppler velocity observation of the flow reversal region is summarized in Figure 1. The spatial extent of the flow reversal region is about 1.5 hour in magnetic local time (MLT) and 5°in MLAT.…”
Section: Observational Resultsmentioning
confidence: 99%
“…This is just for discussing in the simplest way, based on the idea that the strong electric field and the density gradient near the edge of the subauroral trough may be effective in producing the field-aligned irregularities (FAIs). The production of FAIs in the subauroral region is an interesting and important topic [e.g., Greenwald et al, 2006], although detailed discussion on the FAI production itself is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Yizengaw and Moldwin [2005] showed that the equatorward wall of the midlatitude ionospheric trough is magnetically conjugate to the plasmapause, while the opposed temperature and density gradients are the precise conditions for the generation of F region TGI of Hudson and Kelley [1976]. Joint measurements by the Millstone Hill incoherent scatter radar (ISR) and the SuperDARN HF radar located at Wallops Island, Virginia, reported by Greenwald et al [2006] detected decameter-scale irregularities with low drift velocities (< 100 m/s) in the quiet time midlatitude nightside ionosphere. They showed that the irregularities are excited on the equatorward wall of the midlatitude ionospheric trough in a region of opposed density and temperature gradients.…”
Section: Figurementioning
confidence: 99%
“…Although the TGI is a form of universal instability, it can be damped by a conducting layer of the E region ionosphere that shorts out the electrostatic fields. Therefore, the TGI is only observed at night when the E region conductances have very low values [Greenwald et al, 2006].…”
Section: Figurementioning
confidence: 99%
“…Examples of cases when other methods are preferred include backscatter from midlatitude irregularities generated by the temperaturegradient instability (TGI) (Greenwald et al, 2006) and mixed scatter (Ponomarenko et al, 2008). In the most recent study on the issue, Ribeiro et al (2011) have employed the data from the midlatitude SuperDARN radar at Blackstone, Virginia to develop a new method for identifying TGI-generated scatter detected with midlatitude HF radars (defined in that study as being located at magnetic latitudes lower than 60 • ).…”
Section: Instrumentation and Data Post Processingmentioning
confidence: 99%